Reflorestando o saber : produção e plantio de árvores nativas a partir de escola rural no município de Poço Verde Sergipe - Santana, Wesley Cruz (2022)
This study aimed to develop actions of afforestation from the production of native seedlings in the Municipal Agricultural School Professor Dimas Rabelo dos Santos that will be used for afforestation of the school, squares and public roads of the municipality. The town of Poço Verde suffers from irregular rainfall causing prolonged drought, but it has important agricultural areas and is one of the most wooded cities in the state, even so it is important to note that the species used are not native and are being taken to the countryside and villages and can cause damage to the local biome. In the municipality is found the Caatinga vegetation of the hypoxerophilic type, a biome that has a slow regeneration. To develop the research, visits were made to the school area to collect seeds that will serve to form a seed bank for future productions at the school and even for practical classes. Partners were sought to develop the work through public and private agencies, such as the city hall and the city's environment department. The Ipê seedlings that the school received were planted in the Santa Cruz Square and at the school seedlings were planted to start and develop the project. As a product of this research the Mapstree application was developed. It has the capacity to generate geographic points that represent each seedling that were planted, generating in the end a distribution map, in each point the name of the person who planted and the name of the institution that produced the seedling are displayed. With the development of the project, a need for teaching about the native vegetation of the region was identified, as well as its benefits for the flora and the activities involved in this process. The work with the school students allowed an exploration of the theme with subjects in training, being stimulated by the planting of native species both in the school environment and in the city squares. With this project, a very conscious and dynamic work was achieved with the students, who showed interest in the central theme, as well as a partnership with the municipality so that seedlings could be planted in a square.